STUDY ON THE STRUCTURE OF MANGROVE VEGETATION COMMUNITY IN THE VILLAGES OF NUTERI SUBDISTRICT NUMBER OF REGENCY OF BENGKALIS PROVINSI RIAU - Sitorus, Kornelius K; Mulyadi, Aras; Samiaji, Joko (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research be conducted in January 2017. Observation of mangrove forest density and was done in mangrove forest area in Puteri Sembilan Village, North Rupat Sub-district, Bengkalis Regency, Riau Province. The purpose of this research is to know the structure of mangrove vegetation in Desa Puteri Sembilan. In this study concluded that there are 7 species of mangroves namely: Rhizophora mucronata, Bruguiera gymnorhiza. B. sexangula, Kandelia candel, Aegiceras floridum, Amyena gravis and Avicennia alba. Based on the index of type diversity, station I was categorized as low with value of H '= 1,5131. Station II index of diversity of type including low category with value H' = 1,094 and at station III index of diversity type still belongs to low category with value H '= 1, 2284. Keywords: Mangrove, Community Structure Mangrove Vegetation, Bengkalis